Investigation of relationship between organizational commitment and job satisfaction in youth team football coaches in Turkey - Yasar, M. O.; Sunay, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
To develop qualified football players, youth team process has a critical importance. During this process youth team coaches is the key factor. In this point of view the job satisfaction and organizational commitment levels of the youth team coaches are significant to achieve success (Topkaya, 2013). Job satisfaction is, an emotional reaction towards, comparison of the job expectation and what has been acquired the job (Sarminah, 2006). Organizational commitment is definition of employees psychological point of view and relationship between employee and organization. Both of these factors directly influences efficiency of the job. The sample of the study is consisted of 212 youth team coaches who work in Turkey. Coaches were selected by purpose sampling method. The job satisfaction survey which was developed by Spector (1985) and the organizational commitment survey which was developed by Porter et al. (1974) was used. The Cronbach Alpha value of job satisfaction survey was .80 calculated. In addition, non-parametric tests which are Kruskall-Wallis and Mann Whitney-U were used. Job satisfaction and organizational commitment levels of the coaches who participated in this study was found average.There are two remarkable results in this study. When coaches are compared by their education status, it was seen that, higher educated coaches` job satisfaction levels were detected lower. Moreover, when coaches are compared by their football club types, it was found that, professional club coaches, job satisfaction and organizational commitment levels were reached higher than amateur club coaches. It was seen that when age gets older, job satisfaction and organizational commitment levels increase. Also Hickson and Obsehgemi(1999)were found that there was a positive relationship between job satisfaction. According to Ketchan(2001), age and organizational commitment also has a positive relationship.In financial parameters, unexperienced and young coaches satisfaction levels were higher than older experienced coaches. But general results about experience parameter; as the experience gets more the job satisfaction levels increase. In Orhan`s study same results were found. In parallel to these results, when experience is more, the organizational commitment level also increases. ABSTRACT FROM AUTHOR